Integrasi dan Fragmentasi Pengelolaan Sumber Daya Alam (Studi Kasus: Deforestrasi di Brazil) - Warsito, Tulus (Jurnal Hubungan Internasional, 2013)
This paper showed that regional autonomy, which gives an opportunity to region to fully manage natural resources, should be placed in the environmental dimension and position as a global issue. Environmental conditions will be increasingly threatened when environment and natural resources management is solely based on compliance income needs. By doing a comparison of natural resources management policies in Brazil, this paper tries to look at the direction and the relation between management of environmental issues and enforcement of regional autonomy in Indonesia. The case study of deforestation in Brazil show that environmental damage which occurs as a result of natural resources management (forest products) is not only a regional issue in Brazil, but also a national issue, even global issue. This example can be used as a comparison to determine how far regional autonomy should take cares natural resources issue like what happened in Brazil. Regional autonomy is the most fragmented efforts to natural resources, while the globally core of management is integrative efforts.